Ocean governance in the South Pacific region: Progress and plans for action. (May 2017) - Vince, Joanna; Brierley, Elizabeth; Stevenson, Simone; Dunstan, Piers
Abstract: The Pacific Island Regional Ocean Policy (PIROP), which was released in 2002, provided the framework for ocean governance in the Pacific region. Since then there have been a myriad of policy documents and institutional arrangements that have been developed to address ocean governance issues, however, little progress has occurred with regard to the actual implementation of PIROP. This paper examines the region's progress in establishing integrated oceans management, and how this fits with the use of marine spatial planning and area based management tools, such as marine protected areas. It argues that policy making in this region encounters the usual difficulties with integrated policy approaches experienced elsewhere but that these difficulties are further accentuated when applied to developing nations that are highly dependent on external support. It suggests a way forward for the future with development of action plans, implementation and the practical application of those plans including a regional contextualisation/analysis of progress against regional objectives.